Estimating the Impact of the Soviet Union's Threat on the United States– Japan Alliance: A Demand System Approach - Okamura, Minoru (The Review of Economics and Statistics, 1991)
Minoru Okamura, Estimating the Impact of the Soviet Union's Threat on the United States– Japan Alliance: A Demand System Approach, The Review of Economics and Statistics, Vol. 73, No. 2 (May, 1991), pp. 200-207